Dabigatran dibandingkan Warfarin untuk Pencegahan Stroke pada Pasien dengan Atrial Fibrilasi: Laporan Berbasis Bukti - Alvin Nursalim; Yoga Yuniadi (The Indonesian Heart Association, 2011)
Background. Atrial fibrillation (AF) increases the risk of having stroke as high as five fold. Anticoagulant administration such as vitamin K antagonist has been used regularly to reduce the occurence of stroke. Despite the high efficacy, warfarin has several limitations, including a narrow therapeutic window, multiple food and drug interactions, and the need for frequent laboratory monitoring. Dabigatran, an oral thrombin inhibitor, displays some positive characteristics as the solution to warfarin’s limitations.Aim. To determine the efficacy of dabigatran compared to warfarin for stroke prevention in patients with atrial fibrillation.Methods. A search was conducted on PubMed and Google. The selection of title and abstract was done using inclusion and exclusion criteria. Five original articles were found, but only one study was used. The selected study was critically appraised for its validity, importance and applicability.Result. The administration of 150 mg of dabigatran was superior to warfarin with respect of stroke. The relative risk reduction was 36% in the 150 mg dabigatran group. The rate of stroke was 1.01% per year in the group that received 150 mg dabigatran, as compared with 1.57% per year in the warfarin group (relative risk 0.64; 95% confidence interval, 0.51 to 0.81, p<0.001). The administration of dabigatran increased the risk of gastrointestinal bleeding.Conclusion. In patients with atrial fibrillation, dabigatran given at a dose of 150 mg, as compared with warfarin, was associated with lower rate of stroke. Dabigatran administration requires closed gastrointestinal monitoring.